Effects of granular activated carbon on membrane fouling in anaerobic membrane bioreactors - Simarpreet Kaur, Khanijou. (2012)
Anaerobic membrane bioreactors may be viable options in the treatment of various wastewaters. The major drawback of the widespread adoption of such technology is membrane fouling. Carbon dosing has been found to be an effective method in the control of fouling. In this study, it was found that the propensity for fouling was reduced with the addition of granular activated carbon (GAC) in an anaerobic fluidised hollow fiber membrane bioreactor used in the post treatment of effluent from an anaerobic upflow sludge blanket reactor. Under operation of gas recirculation with the addition of GAC, high flux values of up to 66 LMH were achieved without compromising the integrity of the membrane as this registered a maximum transmembrane pressure of just 0.0916 bar. This is due to the gas scouring coupled with GAC scouring against the membrane surface along with the adsorptive capabilities of GAC. Final COD of the permeate was as low as 2.10 mg/L, registering an overall removal efficiency for the two-stage process at 97.3%.